Differences in anthropometric and vertical jump force-time characteristics between U16 and U18 female basketball players - Cabarkapa, Dimitrije; Cabarkapa, Damjana V.; Nagy, Dora; Szabo, Kenza; Balogh, Laszlo; Safar, Sandor; Ratgeber, Laszlo (Frontiers in Sports and Active Living, 2024)
Considering the importance of body composition and lower-body strength and power for basketball players' on-court performance, as well as a lack of sports science research focused on female athletes, the purpose of the present investigation was to record the anthropometric and countermovement vertical jump (CMJ) characteristics of top-tier U16 and U18 female basketball players and examine between-group differences in the aforementioned tests. Thirty-two athletes who were a part of the national basketball academy volunteered to participate in the present investigation. Following the body composition assessment conducted via a segmental multifrequency bioimpedance analyzer, athletes performed three CMJs while standing on a force plate system sampling at 1000 Hz. Independent t-test and Mann-Whitney U test were used to examine betweengroup differences. The findings reveal significant differences in body composition and lower-body neuromuscular performance characteristics between female basketball players ages 16 and 18. Although no differences were observed in muscle and body fat percentages, the U18 group had significantly greater height, overall body mass (both muscle and fat mass), as well as greater segmental fat-free mass (trunk, both legs and arms), intracellular and extracellular water, and body mass index when compared to their U16 counterparts. On the other hand, the U18 group demonstrated longer eccentric, concentric, and braking phase duration, as well as overall contraction time when compared to the U16 players. In addition, the U18 athletes exhibited higher eccentric mean force and power, concentric impulse, peak power, and mean and peak force.